Efeito da moagem de alta energia na microestrutura e nas propriedades magnéticas do compósito wc-10%p.Co - Manuel, João Baptista (2008)
This work a studied the high energy milling effect in microstructure and magnetic properties of the WC-10wt.%Co composite. The composite powders were prepared by mechanical mixed and milled at 2 hours, 100 hours, 200 hours and 300 hours in planetary milling. After this process the composite were compacted in stainless steel die with cylindrical county of 10 mm of diameter, at pressure 200 Mpa and sintered in a resistive furnace in argon atmosphere at 1400 oC for 5 min. The sintered composite were cutted, inlaid, sandpapered, and polished. The microestrutural parameters of the composite was analyzed by X-ray diffraction, scanning electronic microscopy, optical microscopy, hardness, magnetic propriety and Rietveld method analyze. The results shows, with milling time increase the particle size decrease, it possibility minor temperature of sintering. The increase of milling time caused allotropic transformation in cobalt phase and cold welding between particles. The cold welding caused the formation of the particle composite. The X-ray diffraction pattern of composite powders shows the WC peaks intensity decrease with the milling time increase. The X-ray diffraction pattern of the composite sintered samples shows the other phases. The magnetic measurements detected a significant increase in the coercitive field and a decrease in the saturation magnetization with milling time increase. The increase coercitive field it was also verified with decrease grain size with milling time increase. For the composite powders the increase coercitive field it was verified with particle size reduction and saturation magnetization variation is relate with the variation of free cobalt. The Rietveld method analyze shows at milling time increase the mean crystalline size of WC, and Co-cfc phases in composite sintered sample are higher than in composite powders. The mean crystallite size of Co-hc phase in composite powders is higher than in composite sintered sample. The mean lattice strains of WC, Co-hc and Co-cfc phases in composite powders are higher than in composite sintered samples. The cells parameters of the composite powder decrease at milling time increase this effect came from the particle size reduction at milling time increase. In sintered composite the cells parameters is constant with milling time increase